INFLUÊNCIA DE DIFERENTES MATERIAIS REFLETORES EM BANCADAS NA PRODUÇÃO DE MUDAS DE SERINGUEIRA - Souza, Josiane; De Lima, Alexandre Henrique; Costa, Edilson; Da Silva, Bruna Luzia; Junior, Erivaldo José (ANAIS DO ENIC, 2018)
-